An automated screening technique for the detection of sickle-cell haemoglobin. Issue 4 (April 1972) - Canning, D. M.; Crane, R. S.; Huntsman, R. G.; Yawson, G. I.
Abstract : An automated technique is described which is capable of detecting sickle-cell haemoglobin and differentiating the sickle-cell trait from sickle-cell anaemia. The method is based upon the Itano solubility test and utilizes Technicon equipment.